Bioeconomy-based tourism: A new concept responding to the support of bioeconomy - Rinn, Radek; Kalábová, Markéta; Jarský, Vilém (Frontiers in Environmental Science, 2023)
Tourism has experienced dynamic development in recent decades and has become one of the fastest growing industries; however, the Covid-19 pandemic caused unprecedented changes and declines in revenues and tourism trends. With the strong support of bioeconomy (BE) this period brings a great opportunity to transform the entire tourism sector into a model responding to that concept. The main aim of this article is to prove whether and under what possible conditions tourism is a part of the concept of BE. Selected European Union (EU) countries have been chosen so that every geographical area is represented. This analysis was therefore carried out for a total of 12 states and the EU as a whole (13 entities). Of these 13 entities, 7 have their own BE strategy and 6 do not. According to the level of emphasis on the field of tourism in the examined documents, we divided the states into three categories. Although the selected and analysed countries mention tourism in their BE strategies with various emphasis and approach, the inclusion of tourism under this concept is evident. Bioeconomy-based tourism has been designed as a new concept that considers the approach of BE. It focuses above all on a sustainable level of tourism in the connection of economic and environmental pillars, where the main emphasis is placed on the effective use of natural resources and maximum effort not to waste these resources, as well as to support economic growth.